(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Linguistic diversity, also known as linguistic plurality, refers to the coexistence of multiple languages within a specific region or globally. With approximately 7,000 languages worldwide, nearly half are at risk of disappearing, according to UNESCO. While linguistic diversity enriches cultural heritage, it also presents challenges, such as communication barriers and social divisions. Historically, two primary solutions have been used to address these challenges: oral interpretation and written translation, as well as the adoption of a common language. However, both approaches have limitations, including high costs and the potential loss of linguistic identity.